2017
DOI: 10.1371/journal.pone.0178707
|View full text |Cite|
|
Sign up to set email alerts
|

Exposure of bighorn sheep to domestic goats colonized with Mycoplasma ovipneumoniae induces sub-lethal pneumonia

Abstract: BackgroundBronchopneumonia is a population limiting disease of bighorn sheep (Ovis canadensis) that has been associated with contact with domestic Caprinae. The disease is polymicrobial but is initiated by Mycoplasma ovipneumoniae, which is commonly carried by both domestic sheep (O. aries) and goats (Capra aegagrus hircus). However, while previous bighorn sheep comingling studies with domestic sheep have resulted in nearly 100% pneumonia mortality, only sporadic occurrence of fatal pneumonia was reported from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 27 publications
(46 reference statements)
2
25
0
Order By: Relevance
“…In addition, across 12 experimental commingling trials, ~99% of bighorn sheep died from pneumonia after contact with domestic sheep, together providing convincing evidence that contact with domestic sheep is a key risk factor for lethal pneumonia outbreaks in bighorn sheep 22 . A smaller set of experiments have also shown that domestic goats are capable of transmitting the pathogen to bighorn sheep; however the resulting respiratory disease symptoms were of reduced severity, with no fatalities observed 23 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, across 12 experimental commingling trials, ~99% of bighorn sheep died from pneumonia after contact with domestic sheep, together providing convincing evidence that contact with domestic sheep is a key risk factor for lethal pneumonia outbreaks in bighorn sheep 22 . A smaller set of experiments have also shown that domestic goats are capable of transmitting the pathogen to bighorn sheep; however the resulting respiratory disease symptoms were of reduced severity, with no fatalities observed 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Among these species, Mycoplasma ovipneumoniae is the causative agent of chronic, nonprogressive pneumonia, which causes infectious pleuropneumonia in goats and sheep ( 4 ). M. ovipneumoniae has become a worldwide livestock disease and a direct threat to the sheep industry; thus far, no efficient or safe vaccine has been found ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, M. ovipneumoniae infection has been reported in many regions of China, with gradually increasing mortality rates (Handeland et al 2014 ; Besser et al 2014 ). Sheep infected with M. ovipneumoniae show respiratory disorders, runny noses, weight loss, growth retardation, and primary infection within 1–3 months, depending on the age of the sheep (Besser et al 2017 ). The control and prevention of M. ovipneumoniae is difficult and has caused great economic losses to the sheep industry in many countries (Giangaspero et al 2012 ; Xue et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%